2019
DOI: 10.1093/femsle/fnz057
|View full text |Cite
|
Sign up to set email alerts
|

The seagrass holobiont: understanding seagrass-bacteria interactions and their role in seagrass ecosystem functioning

Abstract: This review shows that the presence of seagrass microbial community is critical for the development of seagrasses; from seed germination, through to phytohormone production and enhanced nutrient availability, and defence against pathogens and saprophytes. The tight seagrass-bacterial relationship highlighted in this review supports the existence of a seagrass holobiont and adds to the growing evidence for the importance of marine eukaryotic microorganisms in sustaining vital ecosystems. Incorporating a micro-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 171 publications
3
109
0
Order By: Relevance
“…Daleo et al (2007) showed that mycorrhizal fungi facilitates nutrient uptake in dense-flowered cordgrass (Spartina densiflora). Seagrasses also form symbiotic relationships with a variety of microorganisms (bacteria, archaea, and fungi) both above-and belowground (Venkatachalam et al, 2015;Garcias-Bonet et al, 2016;Tarquinio et al, 2019). For example, seagrass association with sulfideoxidizing bacteria alleviates toxic sulfate accumulation (Cúcio et al, 2016;Martin et al, 2019).…”
Section: Seagrass-microbe Interactionsmentioning
confidence: 99%
“…Daleo et al (2007) showed that mycorrhizal fungi facilitates nutrient uptake in dense-flowered cordgrass (Spartina densiflora). Seagrasses also form symbiotic relationships with a variety of microorganisms (bacteria, archaea, and fungi) both above-and belowground (Venkatachalam et al, 2015;Garcias-Bonet et al, 2016;Tarquinio et al, 2019). For example, seagrass association with sulfideoxidizing bacteria alleviates toxic sulfate accumulation (Cúcio et al, 2016;Martin et al, 2019).…”
Section: Seagrass-microbe Interactionsmentioning
confidence: 99%
“…Seagrass leaves and roots possess a core of epiphytic bacteria which differ from the microbial strains present in the surrounding sediment and seawater environments (Tarquinio et al 2019). The previous study reported that the bacterial diversity in seagrass leaves and roots showed predominant bacterial phyla belonging to Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria (Mishra and Mohanraju 2018;Tarquinio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Seagrasses harbor diverse communities of bacteria including epiphytic and endophytic bacteria symbioses with their leaves and roots. Epiphytic bacteria are nonharmful bacteria that live on the surface of various organs of plants, while endophytic bacteria live inside the plants but have no visibly harmful effects (Tarquinio et al 2019). The epiphytic species provide seagrasses with nitrogen fixation and nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that members of the seagrass microbiome may modulate host growth and response to environmental stresses (15, 18, 19). In addition to fixing nitrogen and producing phytohormones (20, 21), the seagrass microbiome is proposed to mitigate the toxic effects of hydrogen sulfide in sediments, which have been linked to declines in seagrass health and localized die-back events (2224). The seagrass rhizobiome is thought to be primarily influenced by exudation of carbon compounds, which can provide up to 60% of the carbon assimilated by these microbes (25, 26), and by radial oxygen loss from roots, which may promote colonization of the rhizosphere by distinct bacteria (24, 27).…”
Section: Introductionmentioning
confidence: 99%